(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Antimicrobial-resistant bacteria cause severe public health issues and mortalities. The evolution of multi-drug resistant bacteria shifted the focus of researchers towards traditional medicine involving bioactive compounds. Plants with bioactive compounds play a pivotal role in treating human diseases. Many of the plant-based bioactive compounds were proven to have the ability to inhibit bacterial growth through different modes of action. Thus, plant-based compounds have been focused on finding potential molecules with antibacterial efficiency to overcome bacterial infection problems. So, in the present study, phytocompounds of Sida acuta Burm F. leaf extract were identified using GC-MS technique and phytocompounds with antibacterial potential were identified through a molecular docking study. The qualitative test carried out indicated the presence of carbohydrates, alkaloids, phenols, terpenoids, flavonoids, amino acids, steroids, glycosides, saponins, quinones and coumarins in the extract. The GC-MS analysis showed the presence of 30 phytocompounds and molecular docking studies revealed the best binding affinity of the phytocompounds Pyrido[1,2-a]pyrimidine, Acetonitrile,2-(6-phenantridinyl), 5H-Imidazo(2,1-a)isoindole,2-phenyl and Pyrido[1,2-a]pyrimidine towards E. coli biomolecules- 1PHO, 5I5H, 5UW2 and 6NTW respectively. The present study concludes that the phytocompounds of S. acuta have appreciable antibacterial efficiency.